Preparation method and application of Bi / PEDOT / GCE modified electrode

By modifying PEDOT and Bi films on the surface of the glass carbon electrode GCE, Bi/PEDOT/GCE modified electrodes are constructed, which solves the problem of lack of fast and effective trace cadmium ion analysis methods in the prior art, and achieves high sensitivity and high cadmium ions Selective analysis.

CN119413860APending Publication Date: 2025-02-11HAINAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410595560.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-14
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art lacks a modified electrode and analysis method that can quickly and effectively perform trace cadmium ions analysis.

Method used

By modifying polyethylene dioxythiophene PEDOT and bismuth Bi films in sequence on the surface of the glass carbon electrode GCE, Bi/PEDOT/GCE modified electrodes were constructed, and cadmium ion analysis was performed using differential pulse anode dissolution voltammetry DPASV.

Benefits of technology

Fast and effective trace analysis of cadmium ions is achieved, with a detection range of 1nM-40uM and a detection limit of 0.33nM, with high sensitivity and high selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119413860A_ABST
    Figure CN119413860A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a Bi / PEDOT / GCE modified electrode, which comprises the following steps: taking a glassy carbon electrode GCE as a substrate electrode, forming a layer of PEDOT film on the surface of the glassy carbon electrode through a constant potential deposition method, and forming a layer of bismuth nano film on the surface of the modified electrode through an electrodeposition method to prepare the Bi / PEDOT / GCE modified electrode. A glassy carbon electrode (GCE) is used as a substrate, a Bi / PEDOT film is deposited on the surface of the GCE through a potentiostatic deposition method, and a sensing platform with a large specific surface area and excellent conductivity is provided for high-sensitivity and high-selectivity detection of Cd < 2 + > through synergistic modification with Bi and PEDOT, so that rapid and effective trace analysis of Cd < 2 + > is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides preparation and application of a Bi / PEDOT / GCE modified electrode, belonging to the field of nano-electrochemistry and biosensing. Background Art

[0002] Industrial development has induced many environmental pollution problems, causing the content of heavy metals in soil, atmosphere and water to increase continuously. Heavy metal ions cannot be biodegraded and can accumulate in the human body. When the content of heavy metals accumulated in the human body exceeds the standard, it will cause harm to human life and health. Cadmium inhaled by the human body can cause irreversible damage to the liver and kidneys, leading to diseases such as diabetes, rickets and cancer. Therefore, it is very important to detect trace amounts of cadmium ions in the environment. People have developed many detection methods for heavy metal detection, such as atomic absorption spectroscopy, inductively coupled plasma mass spectrometry, inductively coupled plasma emission spectroscopy and fluorescence spectroscopy. Although these traditional methods have good selectivity and sensitivity, there are still problems such as long detection time, complicated operation steps and expensive instruments and equipment. Electrochemical analysis methods have the advantages of simple operation, low cost, high sensitivity and rapid analysis. Therefore, electrochemical analysis methods have become an important detection tool in the detection of trace amounts of heavy metals.

[0003] Electrochemical methods include cyclic voltammetry, square wave voltammetry and differential pulse voltammetry. Among them, differential pulse anodic stripping voltammetry (DPASV) has a lower detection limit and higher sensitivity, so it is widely used to detect heavy metal ions. DPASV is divided into two steps, the enrichment process and the dissolution process. In the first step, the heavy metal ions to be measured are reduced to metals at a certain voltage and enriched on the electrode surface. In the second step, the metal on the electrode surface is oxidized and dissolved back into the solution by potential scanning to generate an oxidation current. In the DPASV test, the working electrode modification material should have a good redox reaction with the target metal. In the past, mercury film modified working electrodes were often used for heavy metal detection, but the strong toxicity of mercury limited its application. Therefore, the study of more environmentally friendly and portable non-mercury electrodes has become a hot topic. In recent years, researchers have found that bismuth film modified electrodes have excellent performance in detecting trace heavy metals, and bismuth film is green and pollution-free and easy to form alloys with heavy metals, so it is more and more widely used. Conductive polymers are often used as modification materials for sensing interfaces because of their good conductivity, simple preparation method and excellent stability. Poly-(3,4-ethylenedioxythiophene) (PEDOT) is the most widely used polythiophene compound. It is widely used in the field of electrochemical analysis due to its high stability and strong adhesion. However, there is currently a lack of a method to achieve the electrochemical analysis of Cd 2+ Modified electrodes and analytical methods for rapid and effective trace analysis. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of Bi / PEDOT / GCE modified electrode to achieve the purpose of Cd 2+ Fast and efficient trace analysis.

[0005] The technical means adopted by the present invention are as follows:

[0006] A preparation method of a Bi / PEDOT / GCE modified electrode comprises the following steps: using a glassy carbon electrode (GCE) as a base electrode, forming a layer of polyethylene dioxythiophene (PEDOT) film on the surface of the glassy carbon electrode by a constant potential deposition method, and forming a layer of bismuth nanofilm on the surface of the modified electrode by an electrodeposition method to prepare a Bi / PEDOT / GCE modified electrode.

[0007] Furthermore, in the process of constructing the modified electrode, the concentration of 3,4-ethylenedioxythiophene EDOT used in constant potential deposition is 0.1 M, the constant potential is 1.0 V, and the polymerization time is 20 to 120 s.

[0008] Furthermore, the Bi(NO3)3 concentration used in the modified electrode construction process is 0.01M, the constant potential is -1.1V, and the electrodeposition time is 30 to 180s.

[0009] Further, the specific steps include:

[0010] (1) Immerse the glassy carbon electrode (GCE) in a mixed solution of 0.1 M 3,4-ethylenedioxythiophene (EDOT) and 0.1 M KCl, polymerize at a constant potential of 1.0 V for 80 s, wash with ultrapure water and dry naturally to obtain a PEDOT / GCE modified electrode;

[0011] (2) The PEDOT / GCE modified electrode was immersed in a 0.01 M Bi(NO3)3 solution with pH 6.5 phosphate buffer solution (PBS) as the supporting electrolyte and deposited at a constant potential of -1.1 V for 120 s. The Bi / PEDOT / GCE modified electrode was obtained after washing with ultrapure water and naturally drying.

[0012] An application of Bi / PEDOT / GCE modified electrode for specific recognition of heavy metal cadmium ions.

[0013] Preferably, during the analytical application of the Bi / PEDOT / GCE modified electrode, the reaction time of the electrode with cadmium ions of different concentrations is 30 to 210 seconds.

[0014] Preferably, the Bi / PEDOT / GCE modified electrode has a good affinity for Cd 2+ The adsorption potential is -0.9~1.5V.

[0015] Preferably, during the analytical application process of the Bi / PEDOT / GCE modified electrode, the electrolyte used for electrochemical detection of cadmium ion electrical signals is 0.1 M phosphate buffer solution PBS, and the pH of the buffer solution is 4.5-8.0.

[0016] Preferably, the specific steps are: placing the Bi / PEDOT / GCE modified electrode in a 0.1 M phosphate buffer solution (PBS) with a pH of 6.5 to perform differential pulse anodic stripping voltammetry (DPASV), developing a working curve, and performing quantitative analysis on actual samples.

[0017] Compared with the prior art, the advantages of the present invention are:

[0018] The present invention adopts GCE as the base electrode, and sequentially modifies PEDOT and Bi on its surface to increase the specific surface area of ​​the electrode and improve its conductive performance, thereby constructing a high-sensitivity trace detection method for Cd 2+ The electrochemical sensor was applied to the Cd in real seawater samples. 2+ The detection range of trace analysis was 1nM-40uM and the detection limit was 0.33nM.

[0019] The present invention uses an electrochemical deposition method to polymerize PEDOT on a glassy carbon electrode, and further electroplating a bismuth film on the PEDOT film to construct an electrochemical aptamer sensor. Using a glassy carbon electrode (GCE) as a substrate, a Bi / PEDOT film is deposited on the GCE surface by a constant potential deposition method, and the Bi and PEDOT are synergistically modified into Cd 2+ The highly sensitive and selective detection of Cd provides a sensing platform with a large specific surface area and excellent conductivity, thereby realizing 2+ Fast and efficient trace analysis.

[0020] The specific manifestations are:

[0021] (1) The two nanomaterials used in the Bi / PEDOT / GCE modified electrode prepared by the present invention can exert a synergistic effect. Their superior conductivity can enhance the sensitivity of the sensing interface; their large specific surface area has more heavy metal ion binding sites, which can achieve the amplification of electrical signals;

[0022] (2) The present invention directly generates an electrodeposited PEDOT film on the GCE substrate electrode by a constant potential deposition method, and further directly electrodeposit a Bi nanofilm by an electrodeposition method, which has the advantages of simple process, low cost, short cycle, and low energy consumption.

[0023] (3) The present invention uses DPASV to perform quantitative analysis on cadmium ions, with a wide detection range (1nM-40uM) and a low detection limit (0.33nM). BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Scanning electron microscopy images of electrode interfaces modified with different materials; (A) PEDOT / GCE, (B) Bi / GCE, (C) Bi / PEDOT / GCE.

[0025] Figure 2-1 At 1.0mmol / L[Fe(CN)6] 3- / 4- and cyclic voltammograms in 1.0 mol / L KCl electrolyte; (a) GCE, (b) Bi / GCE, (c) PEDOT / GCE, (d) Bi / PEDOT / GCE, the scan rate is 0.10 V / s.

[0026] Figure 2-2 For Bi / PEDOT / GCE in 1.0mmol / L[Fe(CN)6] 3- / 4- Cyclic voltammetry curves at different scan rates in 1.0 mol / L KCl electrolyte.

[0027] Figure 2-3 For different modified electrodes in 5mM [Fe(CN)6] 3- / 4- And electrochemical impedance spectroscopy curves in 0.1M KCl solution.

[0028] Figure 3 For GCE, Bi / GCE, PEDOT / GCE, Bi / PEDOT / GCE at 40 μM Cd 2+ DPASV curve graph in .

[0029] Figure 4-1 DPASV analysis diagram of PEDOT at different deposition times.

[0030] Figure 4-2 DPASV analysis diagram of Bi at different film forming times.

[0031] Figure 4-3 DPASV analysis diagram of 0.1M supporting electrolyte types (BR, HAc-NaAC, PBS, Tirs-HCl).

[0032] Figure 4-4 Graph of DPASV analysis for pH values ​​of PBS.

[0033] Figure 4-5 DPASV analysis diagram of deposition potential.

[0034] Figure 4-6 DPASV analysis diagram of deposition time.

[0035] Figure 5-1 For different concentrations of Cd 2+DPASV curve graph; 1nM, 10nM, 100nM, 200nM, 400nM, 600nM, 800nM, 1μM, 2μM, 4μM, 6μM, 8μM, 10μM, 20μM, 30μM, 40μM.

[0036] Figure 5-2 Ip and Cd 2+ Linear relationship graph of concentration. DETAILED DESCRIPTION

[0037] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0038] Example 1

[0039] Immerse GCE in a mixed solution of 0.1MEDOT and 0.1MKCl, polymerize at a constant potential of 1.0V for 80s, wash with ultrapure water and dry naturally to obtain PEDOT / GCE; then immerse PEDOT / GCE in 0.01M Bi(NO3)3 solution, use PBS (PH6.5) as a supporting electrolyte, deposit at a constant potential of -1.1V for 120s, wash with ultrapure water and dry naturally to obtain Bi / PEDOT / GCE.

[0040] Comparative Example 1

[0041] The GCE was immersed in 0.01M Bi(NO3)3 solution with PBS (PH 6.5) as the supporting electrolyte, deposited at a constant potential of -1.1V for 120s, washed with ultrapure water and naturally dried to obtain Bi / GCE.

[0042] Comparative Example 2

[0043] The GCE was immersed in a mixed solution of 0.1MEDOT and 0.1MKCl, polymerized at a constant potential of 1.0 V for 80 s, washed with ultrapure water and naturally dried to obtain PEDOT / GCE.

[0044] Characterization analysis

[0045] 1. Scanning electron microscopy characterization

[0046] Figure 1 A is the surface morphology SEM image of the PEDOT / GCE electrode, which appears as a smooth plane composed of nano-spherical particles. Figure 1 B is the surface morphology of the Bi / GCE electrode, which is a dendritic dispersed structure composed of nanorod-like substances. Figure 1C is the surface morphology of the Bi / PEDOT / GCE electrode. We can see that after composite deposition, the morphology changes significantly. The PEDOT nanospheres and Bi nanorods are closely arranged to form a uniform porous network structure. The network structure increases the specific surface area and increases the heavy metal ion binding sites, further increasing the heavy metal ion enrichment capacity.

[0047] 2. Electrochemical Characterization

[0048] In 1.0 mM [Fe(CN)6] 3- / 4- In solution, cyclic voltammetry (CV) was performed on bare GCE, Bi / GCE, PEDOT / GCE and Bi / PEDOT / GCE. Figure 2-1 ). The results show that the Bi / PEDOT / GCE electrode has the highest peak current, which is about 1.25 times that of bare GCE. This shows that the porous network structure formed by the composite deposition of Bi nanosheets and PEDOT rod-shaped particles has a larger specific surface area, which improves the electron transfer rate of the electrode. It proves that the Bi / PEDOT / GCE electrode has better electrochemical catalytic performance.

[0049] To further confirm the increase in electroactive surface area (A), 1.0 mM [Fe(CN)6] 3- / 4- In the solution, CV of Bi / PEDOT / GCE at different scanning speeds was performed. From the recorded CV curves ( Figure 2-2 )

[0050] The reduction peak current increases linearly with the square root of the scan rate. According to the Randles-Sevcik equation:

[0051] I p =2.69×10 6 n 3 / 2 ACD 1 / 2 ν 1 / 2

[0052] Among them I p is the anodic peak current (μA), n is the number of transferred electrons (in [Fe(CN)6] 3- / 4- The number of redox transfer electrons in the solution system is n = 1), and A is the electroactive surface area (cm 2 ), C is [Fe(CN)6] 3- / 4- The concentration (1.0×10 -6 mol / cm 3 ), D is [Fe(CN)6] 3- / 4- Diffusion coefficient (6.7×10-6cm 2 / s), v is the scanning rate (V / s).p and v 1 / 2 The slope of can be calculated to obtain the electroactive surface area (A) of Bi / PEDOT / GCE to be 0.0886 cm 2 , larger than 0.0629cm of bare GCE 2 The data show that the presence of Bi and PEDOT increases the electroactive surface area of ​​the glassy carbon electrode, providing more active sites for the subsequent enrichment of heavy metal ions.

[0053] In the presence of 5 mM [Fe(CN)6] 3- / 4- and 0.1M KCl solution, the electrochemical impedance spectroscopy was used to detect the different modified electrodes from 10kHz to 0.05Hz. Figure 2-3 As shown in the figure, the diameter of the semicircle in the high-frequency part indicates the charge transfer resistance of the electrode interface, which is the process of electron transfer kinetics of potassium ferrocyanide probe on the modified electrode surface. Compared with the bare GCE electrode, the reduced Rct value of the Bi / PEDOT / GCE electrode proves that the Bi+PEDOT composite material has good conductivity.

[0054] Three CDs 2+ The electrochemical behavior

[0055] Figure 3 Displays Cd 2+ DPASV curves on bare GCE, Bi / GCE, PEDOT / GCE, and Bi / PEDOT / GCE electrodes. DPASV is the process of reducing metal ions to metals attached to the electrode surface and oxidizing the metals to generate oxidation current during the dissolution process. 2+ In solution, the oxidation peak current of bare GCE is weak. After Bi and PEDOT are modified on the GCE surface, Cd 2+ The increase in oxidation peak current proves that Bi and PEDOT have a positive effect on metal ion accumulation. In addition, the oxidation peak current of Bi / PEDOT / GCE is significantly stronger than that of Bi / GCE and PEDOT / GCE, indicating that the Bi and PEDOT composite material has a synergistic positive effect in the electrochemical analysis of metal ions, including the formation of a larger specific surface area and a better electron transfer rate. Bi can form an alloy with cadmium to enhance the 2+ The PEDOT-modified glassy carbon electrode increases the adhesion of the bismuth film on the electrode, which improves the sensitivity of the composite electrode and has better detection performance.

[0056] 4. Optimization of modified electrode preparation conditions

[0057] In order to obtain Cd 2+The maximum response current was obtained by optimizing the PEDOT deposition time, Bi film formation time, buffer solution selection, buffer solution pH, deposition potential and time. The oxidation peak current was used as the ordinate and the various parameters were used as the abscissa. First, the PEDOT deposition time was investigated. The experimental results are shown in Figure 1. Figure 4-1 As shown, the deposition time is 20 to 120 seconds, Cd 2+ The oxidation peak current increases first and then decreases with the PEDOT deposition time. The oxidation peak current reaches the maximum at 80 s, indicating that the thickness of the PEDOT film has an important effect on the Cd 2+ The adsorption of bismuth has a great influence on the adsorption of bismuth. Therefore, this paper selects the optimal deposition time of PEDOT as 80s. At the same time, the film formation time of Bi is studied. The experimental results are as follows Figure 4-2 As shown, the deposition time ranges from 30 to 180 s, Cd 2+ The oxidation peak current of Cd increases first and then decreases with the increase of Bi film forming time. 2+ The oxidation peak current value is the largest. Therefore, this paper selects Bi film deposition for 120s as the optimal condition.

[0058] Secondly, the effects of different buffer solutions on Cd 2+ The influence of dissolution response was studied. BR, HAc-NaAC, PBS, and Tirs-HCl buffer solutions were selected as the research objects. The experimental results are shown in Figure 4-3 As shown in the figure, the peak current of PBS buffer solution is the largest, so this paper selects 0.1M PBS buffer solution as the optimal buffer solution system. The pH value of the buffer solution was further optimized and tested to study the Cd 2+ The oxidation peak current in the pH range of 4.5 to 8, the experimental results are as follows Figure 4-4 As shown, when pH is 6.5, Cd 2+ The dissolution peak current value is the largest. Therefore, this paper selects PBS at pH 6.5 as the best buffer solution for the experiment.

[0059] When DPASV is used to analyze heavy metals, deposition potential is an important factor. 2+ The adsorption potential was optimized. Figure 4-5 As shown, in the potential range of -0.9 to -1.5 V, Cd 2+ The oxidation peak current of Cd increases and then decreases. 2+ Therefore, this experiment selected -1.3V as the Cd 2+ The optimal adsorption potential of Cd was studied in this paper. 2+ The influence of electrochemical signals. Figure 4-6 As shown, between 30 and 210 seconds, Cd 2+The oxidation peak current increases first and then decreases with the increase of deposition time, reaching the maximum at 150s. It can be determined that 150s is the peak current of Cd 2+ The best deposition time.

[0060] 5. Working curve

[0061] By optimizing the experimental conditions, the detection of different concentrations of Cd under the best experimental conditions was studied. 2+ The DPASV curve is as follows: Figure 5-1 shown. Figure 5-2 Cd 2+ The linear graph of Figure 5-2 It can be seen that the DPASV peak current and Cd 2+ The concentration increases linearly between 1nM and 40uM. However, there is an inflection point at 10uM, and the linear equation is divided into two segments with different slopes. 2+ When the concentration is greater than 10uM, the growth trend slows down significantly, but the peak current is similar to Cd 2+ The concentration is proportional to Cd 2+ The linear equation for concentrations in the range of 1nM-10uM is: p =20.04c-6.04(R2=0.982),Cd 2+ The linear equation for concentrations in the range of 10uM-40uM is: p =5.25c+159(R2=0.995). According to the signal-to-noise ratio (S / N=3), the lowest detection limit of the modified electrode was calculated to be 0.33 nM.

[0062] 6. Sample testing

[0063] The prepared Bi / PEDOT / GCE electrode was used to detect Cd in seawater samples. 2+ Quantitative analysis of Cd using seawater as solvent 2 + The standard solution was diluted and the Cd content in the sample solution was determined by the standard addition method. 2+ The recovery rate was between 56.8% and 118.5%, indicating that the constructed electrochemical sensor can be well used for Cd in water samples. 2+ Determination of content.

[0064] In summary, the present invention uses GCE as the substrate electrode, and sequentially modifies PEDOT and Bi on its surface to increase the specific surface area of ​​the electrode and improve its conductivity, thus constructing a highly sensitive electrochemical sensor, which is successfully applied to the detection of Cd in actual seawater samples. 2+ Quantitative analysis of .

[0065] Due to the synergistic effect of the composite conductive materials, the composite electrode 2+It shows good electrochemical response. In the concentration range of 1nM-40uM, the cadmium ion concentration and peak current show a good linear relationship, and the minimum detection limit is 0.33nM. The Bi / PEDOT / GC sensor can be used to quickly determine trace cadmium ions with a very low detection limit and excellent repeatability and stability.

[0066] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a Bi / PEDOT / GCE modified electrode, characterized in that: The following steps are involved: With glassy carbon electrode GCE as the base electrode, a polyethylene dioxythiophene (PEDOT) film was formed on the surface of the glassy carbon electrode by constant potential deposition, and a bismuth nanofilm was formed on the surface of the modified electrode by electrodeposition to prepare a Bi / PEDOT / GCE modified electrode.

2. The method for preparing a Bi / PEDOT / GCE modified electrode according to claim 1, characterized in that: The concentration of 3,4-ethylenedioxythiophene EDOT used in the constant potential deposition during the construction of the modified electrode is 0.1M, the constant potential is 1.0V, and the polymerization time is 20 to 120s.

3. The method for preparing a Bi / PEDOT / GCE modified electrode according to claim 1, characterized in that: The concentration of Bi(NO3)3 used in the modified electrode construction process is 0.01M, the constant potential is -1.1V, and the electrodeposition time is 30 to 180s.

4. A method for preparing a Bi / PEDOT / GCE modified electrode according to any one of claims 1 to 3, characterized in that: The specific steps include: (1) Immerse the glassy carbon electrode (GCE) in a mixed solution of 0.1 M 3,4-ethylenedioxythiophene (EDOT) and 0.1 M KCl, polymerize at a constant potential of 1.0 V for 80 s, wash with ultrapure water and dry naturally to obtain a PEDOT / GCE modified electrode; (2) The PEDOT / GCE modified electrode was immersed in a 0.01 M Bi(NO3)3 solution with pH 6.5 phosphate buffer solution (PBS) as the supporting electrolyte and deposited at a constant potential of -1.1 V for 120 s. The Bi / PEDOT / GCE modified electrode was obtained after washing with ultrapure water and naturally drying.

5. An application of Bi / PEDOT / GCE modified electrode, characterized in that: Used to specifically identify heavy metal cadmium ions.

6. The use of a Bi / PEDOT / GCE modified electrode according to claim 5, characterized in that: During analytical applications, the reaction time of the Bi / PEDOT / GCE modified electrode with cadmium ions of different concentrations is 30 to 210 seconds.

7. The use of a Bi / PEDOT / GCE modified electrode according to claim 5, characterized in that: In the analytical application process, the Bi / PEDOT / GCE modified electrode has a good 2+ The adsorption potential is -0.9~1.5V.

8. The use of a Bi / PEDOT / GCE modified electrode according to claim 5, characterized in that: During the analytical application of the Bi / PEDOT / GCE modified electrode, the electrolyte used for electrochemical detection of cadmium ion electrical signals is 0.1 M phosphate buffer solution PBS, and the pH of the buffer solution is 4.5-8.

0.

9. The use of a Bi / PEDOT / GCE modified electrode according to claims 5-8, characterized in that: Specific steps: The Bi / PEDOT / GCE modified electrode was placed in 0.1 M phosphate buffer solution (PBS) with a pH of 6.5 for differential pulse anodic stripping voltammetry (DPASV). A working curve was developed and quantitative analysis of actual samples was performed.